Dampak Kebijakan Pembangunan Ekonomi terhadap Ketimpangan Pendapatan dan Kesejahteraan Masyarakat di Kota - Abdul Aziz; Ahmad Yusuf Akbar; Jumhar Daulay; Anugerah Panji Ahmad (CEMERLANG : Jurnal Manajemen dan Ekonomi Bisnis, 2025)
This study aims to analyze the impact of economic development policies on income inequality and the welfare of the community in Medan City. Using a qualitative method, this research examines how the economic development policies implemented by the local government affect income distribution and social welfare among the city’s residents. The data used in this study were obtained from 10 interviews with respondents consisting of community members, community leaders, and relevant local government officials, as well as regional economic statistical data. The analysis identifies the relationship between the implemented economic policies and changes in income inequality and quality of life, and explores the factors influencing the success or failure of these policies. The findings indicate that, although there has been progress in economic development, income inequality remains significant, with many of the less fortunate citizens still not fully benefiting from the development policies. Therefore, this study provides recommendations for the local government to formulate more inclusive and equitable policies to reduce economic disparities and improve the welfare of the community more effectively. This research is expected to contribute to the formulation of more targeted policies aimed at addressing social and economic disparities in the future.